Green harms and crimes : critical criminology in a changing world - Sollund, Ragnhild Aslaug, 1959-; Cohen, Stanley (Critical criminological perspectives., 2015)
Green Harms and Crimes was produced to celebrate the 40th anniversary of the European Group for the Study of Deviance and Social Control, and to pay tribute to Stan Cohen. The book presents discussions of the application of Cohen's theories alongside empirical contributions in the fields of critical and green criminology. Taken together, the authors address harms and crimes against the environment, as well as against human and nonhuman victims. Injustices produced by powers driving harmful practices, such as capitalism and consumerism, are analyzed from the perspectives of speciesism, environmental (in)justice, species (in)justice and ecological (in)justice - thus encompassing both human and animal rights. Specific topics in this important volume include: waste and corporate crimes, agribusiness and food crimes, illegal wildlife trafficking, species endangerment, political protest and its oppression by legal power institutions.